Attitude of Rural Community Towards Health Care Utilization at Primary (Journal of Medicine, 2008)
Objective: The study was conducted to assess the attitude of rural community towards health care utilization at primary level public health facilities. Study Design: Descriptive cross sectional study carried out over a period of six months from June to November 2007. Study Setting: A randomly selected village (Lohagach) of Sreepur Upazila under Gazipur district. Subjects: 305 randomly selected adult (age 15-60 years) household members who are permanent residents of the said area. Materials and methods: Data was collected by face to face interview with a semi-structured questionnaire. Results: Among the 305 respondents, 55.40% are male and 44.60% are female with mean age of 32.39 years (± SD 11.94). Most respondents have educational qualification up to secondary level (32.10%) while some up to primary level (21%). Majority of the respondents are housewives (35.40%) and Service holders (20.30%) having an average monthly family income of TK.7805.57 (± SD 6442.24). It is evident from the study that; females, respondents from older age group, and those from higher monthly family income has less appreciation for existing primary level public health facilities. Also, the higher the education level of the respondent, the lower was the level of satisfaction regarding healthcare received at primary level public health facilities. As regards to availability of healthcare; insufficiency of doctors (52.8%) & prescribed medicine supply (75.4%) and lack of appropriate and necessary laboratory investigation (64.6%) & surgical treatment facilities (62.6%) are identified by the respondents as major setbacks. The study reveals key impediments pointed out by the respondents which interfere with their easy access to quality healthcare at these facilities; including long waiting time (60.3%), insufficient waiting room facilities (64.9%) and inadequate duration of consultation with physician (50.2%). Major constraints associated with primary health care utilization are mostly due to lack of awareness (22.66%) and transportation problem (22.6%). Key words: Attitude of Rural Community, Health Care Utilization, Primary Level Public Health Facilities DOI = 10.3329/jom.v9i2.1433 J MEDICINE 2008; 9 : 69-74